Initial Rotational Instability of the Tapered Wedge-Shaped Type Cementless Stem - Yosuke Iwamoto; Hiroaki Kijima; Hiroshi Tazawa; Natsuo Konishi; Hitoshi Kubota; Shin Yamada; Takayuki Tani; Keiji Kamo; Norio Suzuki; Yoshihiko Okudera; Masashi Fujii; Ken Sasaki; et al. (Advances in Orthopedics)
Background. Because the tapered wedge-shaped type cementless stem has a small anteroposterior width and a low occupation rate in the medullary space, postoperative rotational instability and stem subsidence due to inadequate proximal fixation are concerns. The purpose of this study was to clarify the relationship between the rotational instability of the tapered wedge-shaped type cementless stem and femoral canal shape. Methods. A total of 61 primary total hip arthroplasties with the tapered wedge-shaped type cementless stem Accolade® TMZF (11 males, 50 females; mean age 60 years) from January 2012 to June 2015 who underwent computed tomography before surgery and within 4 weeks and 1 year after surgery were evaluated. The preoperative femoral neck anteversion angle, preoperative femoral canal flair index, the degree of postoperative stem subsidence within 1 year after operation, and the degree of rotational change in the stem setting angle within 1 year after operation were investigated. Results. The mean preoperative femoral neck anteversion angle was 32.2° ± 17.8° (0°–69°), and the mean preoperative canal flair index was 3.68 ± 0.58 (2.44–5.55). There were no stem subsidence cases within 1 year after operation. The mean degree of rotational change in the stem from immediately to 1 year after surgery was −0.4° ± 1.7° (−3°–3°). There was no significant correlation between the canal flair index and the rotational change in the stem. In addition, the mean difference between the preoperative femoral neck anteversion angle and the stem rotational angle immediately after surgery was only 1.3° ± 5.3° (−29°–15°). Conclusions. In all cases, including stove-pipe cases, the degree of rotational change in the Accolade® TMZF stem from immediately to 1 year after surgery was within 3°. In other words, regardless of femoral canal shape, the tapered wedge-shaped type cementless stem has little initial rotational instability.